1980
DOI: 10.2527/jas1980.503428x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Maternal Environmental Factors Influencing Litter Size and Reproductive Efficiency in Mice

Abstract: Lines of mice which have been genetically differentiated in litter size at birth and 6-week body weight by single-trait or index selection were randomly assigned to be reared in postnatal litter sizes (PLS) of N8, N12 or N16. The lines were selected as follows: large litter size (L+), large 6-week body weight (W+), selection index to decrease litter size and increase 6-week body weight (L-W+), selection index to increase litter size and decrease 6-week weight (L+W-) and random selection (K). Line and PLS diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
11
0

Year Published

1980
1980
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 0 publications
6
11
0
Order By: Relevance
“…The realized differentials for UT were considerably smaller than those exhibited in the IX and LS criteria (6.2, 12.8, and 10.8 g, respectively) but larger than unintentional selection in LC (.5 g). The higher values in the IX and LS criteria are in agreement with the findings of Eisen and Durrant (1980); their study indicated that improved female reproductive performance, especially ovulation rate, was correlated with increased body size.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…The realized differentials for UT were considerably smaller than those exhibited in the IX and LS criteria (6.2, 12.8, and 10.8 g, respectively) but larger than unintentional selection in LC (.5 g). The higher values in the IX and LS criteria are in agreement with the findings of Eisen and Durrant (1980); their study indicated that improved female reproductive performance, especially ovulation rate, was correlated with increased body size.…”
Section: Resultssupporting
confidence: 79%
“…The resulting changes after 21 generations of selection were larger than those noted at Generation 13. Eisen and Durrant (1980) found that for each additional gram of BW at mating, litter size increased by .42 pups. In the present study, total number born was regressed on female mating weight, and regression coefficients for M, UT, LS, and LC, replicates pooled, were .37 f .13 ( P < .11), .24 _+ .04 ( P < .05),…”
Section: Resultsmentioning
confidence: 99%
“…They range from o to 0.62, depending on which group one examines; our maximum values are similar in magnitude to those found by Anderson (1975) for Microtus townsendii. However, Anderson's results were based on full-sib estimates for the most part, and the consistent maternal effects demonstrated here and in other quantitative-genetic studies of domestic rodents (Eisen and Durrant, 1980;Falconer, 1981) make it almost certain that her estimates were high. For our data, the full-sib heritability is twice the sum of the sire and dam components.…”
Section: Discussionsupporting
confidence: 75%
“…Improvements in litter size in mice have occurred from direct selection (Falconer, 1955(Falconer, , 1965(Falconer, , 1971Bradford, 1968Bradford, , 1979Joakimsen and Baker, 1977;Bakker et al 1978;Eisen and Durrant, 1980) and from selection for embryo (fetal) survival rate (Bradford, 1969(Bradford, , 1979. Responses from direct selection have been attributed largely to increased ovulation rate and stable or increasing survival rate (Bakker et al, 1978;Bradford, 1979).…”
Section: Discussionmentioning
confidence: 99%